Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional, Profitabilitas dan Likuiditas terhadap Kebijakan Hutang - Khofiyah, Qorri A’ina; Mahirun, Mahirun; Ahliansyah, Muhammad Rafli (LPPM Universitas Pekalongan, 2024)
This study aims to test and analyze the factors that influence debt policy involving managerial ownership, institutional ownership, profitability, and liquidity variables in companies indexed IDX30 on the Indonesia Stock Exchange for the period 2018-2022. The analytical tool we use is multiple linear regression on SPPS software to test the effect of the independent variable on the dependent variable. The findings in this study are institutional ownership, managerial ownership, and current ratio have a negative and significant effect. Meanwhile, another finding of our study is that profitability with the return on assets indicator also has a negative although insignificant effect on corporate debt policy.